Conservation of palm wine using ultraviolet radiation - Nnanwube, Ikechukwu; Keke, Mabel (Goodwood Publishing, 2024)
Purpose: This study aimed to explore the effectiveness of ultraviolet (UV) radiation in the conservation of palm wine by reducing its microbial load, specifically mold, yeast, and bacteria. Research Methodology: Palm wine was conserved by sterilization with ultraviolet rays. The time of contact of the rays and the intensity of the rays with palm wine were varied. The microorganisms considered include molds, yeasts, and bacteria. Results: The results showed that the microbial load of sterilized palm wine decreased with time of contact with the rays. The microbial load of the wine before and after sterilization was determined. Moreover, the microbial load further decreased during the storage of the sterilized samples. In fact, sterilization time of 240 seconds (4 minutes) reduced the mould and yeast from to and then to zero after 10 days of preservation. Conclusions: UV radiation is an effective method for reducing microbial contamination in palm wine, with an optimal sterilization time of 240 s providing the best results. This sterilization process not only reduced microbial presence immediately but also extended the shelf life of palm wine during storage. Limitations: This study did not examine the impact of stirring palm wine during sterilization on microbial load reduction, which could potentially influence the treatment’s effectiveness. Contribution: This study established an ideal sterilization time of 240 s (4 min) for palm wine, providing an effective method for its preservation and ensuring its safety for consumption.